Effects of Spatially Varying Seismic Ground Motions and Incident Angles on Behavior of Long Tunnels - Yundong Zhou; Yongxin Wu; Ziheng Shangguan; Zhanbin Wang (Advances in Civil Engineering)
Seismic behavior of long circle tunnels is significantly influenced by the nature of input motion. This study, based on the 3D finite-element method (FEM), evaluates the effects of spatially varying seismic ground motions and uniform input seismic ground motions and their incident angles on the diameter strain rate and tensive/compressive principal stresses under different strata. It is found that (1) the spatially varying seismic ground motions induced larger diameter strain rate (radially deformation) than the uniform input seismic motion, (2) the spatially varying seismic ground motions had an asymmetric effect on the radial strain rate distributions, and (3) the rising incident angles changed the pure shear stress state into a complex stress state for tunnels under specified input motion.